Impact of Time of Surgery on the Outcome after Surgical Stabilization of Rib Fractures in Severely Injured Patients with Severe Chest Trauma—A Matched-Pairs Analysis of the German Trauma Registry - Becker, L.; Schulz-Drost, S.; Spering, C.; Franke, A.; Dudda, M.; Kamp, O.; Lefering, R.; Matthes, G.; Bieler, D., on behalf of the Committee on Emergency Medicine, Intensive Care and Trauma Management (Sektion NIS) of the German Trauma Society (DGU) (Frontiers in Surgery, 2022)
Purpose: In severely injured patients with multiple rib fractures the beneficial effect of surgical stabilization is still unknown. The existing literature shows divergent results and the indication and especially the right timing of an operation are subject of a broad discussion. The aim of this study was to determine the influence of the time point of a surgical stabilization of rib fractures (SSRF) on the outcome in a multi-center database with special regard to the duration of ventilation, intensive care and overall hospital stay. Methods: Data from the TraumaRegister DGU® collected between 2010 and 2019 were used to evaluate patients over 16 years of age with severe rib fractures (AIS ≥3) who received a SSRF in a matched-pairs analysis. In this matched-pairs analysis we compared the effects of an early SSRF within 48 h after initial trauma vs. late SSRF 3-10 days after trauma. Results: After the selection process we were able to find 142 matched-pairs for further evaluation. Early SSRF was associated with a significantly shorter length of stay in the intensive care unit (16.2 d vs. 12.7 d, p=0,020) and the overall hospital stay (28.5 d vs. 23.4 d, p=0.005) was significantly longer in the group with late SSRF. Concerning the days on mechanical ventilation we were able to demonstrate a trend for an approximately 1.5 d shorter ventilation time for patients after early SSRF although this difference was not statistically significant (p=0,226). Conclusions: We were able to determine the significant beneficial effects of early SSRF resulting in a shorter ICU stay and a shorter LOS in hospital and additionally a trend to a shorter time on mechanical ventilation.